An Analysis of Students’ Ability in Writing Recount Text to The Eighth Graders in MTs Mambaul Ulum Kubupadi - Suryati, Suryati; Nizarrahmadi, Nizarrahmadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
An analysis of students‟ ability in writing recount text. The purpose of the research was to know the students‟ ability in wiring recount text of the eighth-grade student of MTs Mambaul Ulum at Kubupadi. The method used in this research was a descriptive qualitative which the researcher explained the result of research by describing the data gained. The techniques used for collecting data were observation and test. The tool of collecting data were written test. Based on the finding in this research, the students in the eighth grade of MTs Mambaul Ulum Kubupadi have good ability in writing recount text, with a total average score of 21. The score is 22 score at writing organization of the text, 21 score at content, 19 score at grammar and 20 score at vocabulary.